1995
DOI: 10.1038/bjc.1995.280
|View full text |Cite
|
Sign up to set email alerts
|

AQ4N: an alkylaminoanthraquinone N-oxide showing bioreductive potential and positive interaction with radiation in vivo

Abstract: S-y AQ4N (l,4-bLs-q25ddimthyai oo y}amin5dydroxy-anthrane-9,10-dione) is a novel alkylaminoanthraquinone N-oxide which, on reducin, forms a stable DNA affinic cytotoxi compound AQ4. The The failure to cure tumours with radiotherapy and chemotherapy has been attributed in part to the presence of treatment-resistant subpopulations of hypoxic tumour cells (Bush et at., 1978). Bioreductive agents provide a novel approach to this problem: reduction of the prodrug within a hypoxic cell to produce a cytotoxic metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(57 citation statements)
references
References 12 publications
3
52
0
1
Order By: Relevance
“…It was observed that normoxic mice tolerated single doses up to 320 mg kg -1 in the hypobaric chamber experiments (McKeown et al, 1995). In two studies over 400 mg kg -1 was tolerated (Wilson et al, 1996, Bibby, personal communication); this has since been confirmed by preclinical toxicity trials carried out by BIBRA (personal communication).…”
Section: Aq4n: Defining a Maximum Tolerated Dose In Vivomentioning
confidence: 92%
See 3 more Smart Citations
“…It was observed that normoxic mice tolerated single doses up to 320 mg kg -1 in the hypobaric chamber experiments (McKeown et al, 1995). In two studies over 400 mg kg -1 was tolerated (Wilson et al, 1996, Bibby, personal communication); this has since been confirmed by preclinical toxicity trials carried out by BIBRA (personal communication).…”
Section: Aq4n: Defining a Maximum Tolerated Dose In Vivomentioning
confidence: 92%
“…When combined with radiation in vivo a substantial enhancement of antitumour efficacy is observed with a dose modification factor of about two. This enhancement is found irrespective of whether AQ4N is administered before or after the radiation exposure providing strong evidence that this agent does act as a bioreductive cytotoxin (Figure 2; McKeown et al, 1995McKeown et al, , 1996 Tumour growth delay when AQ4N was administered before or after a single dose of radiation (12 Gy). AQ4N (200 mg kg -1 ) was administered at a range of times up to 120 h before and 48 h after a single dose of X-irradiation (12 Gy).…”
Section: Aq4n In Combination With Radiation or Chemotherapeutic Agentmentioning
confidence: 92%
See 2 more Smart Citations
“…iNOS is found in elevated levels in mammalian tumours [8][9][10] and employing an antisense gene therapy approach could lead to a constriction in tumour vessels and subsequent decrease in oxygenation levels. This artificially hypoxic tumour environment could then be targeted with any novel bioreductive drugs (eg AQ4N 27 ) subsequently shown to be effective in the clinic.…”
Section: Gene Therapymentioning
confidence: 99%